An overview of surgical sealant devices: current approaches and future trends. (3rd October 2018) - Heher, Philipp; Ferguson, James; Redl, Heinz; Slezak, Paul
ABSTRACT: Introduction : Wound leakage is a common complication after surgical incision or resection. In the past, a variety of clinically-approved surgical sealant devices have been used as an adjunct or alternative to conventional means of tissue sealing. However, there is still an unmet need for a sealant that can be universally applied over a wide range of clinical applications. This has further driven the emergence of both novel liquid surgical sealant devices and active hemostatic sealant patches to deal with the increasing complexity of surgical interventions in the field of hemorrhage control and wound leakage. Areas covered : Emphasizing the literature from the past 5 years, this review covers the current offering of natural, synthetic or composite surgical sealant devices in liquid or patch form, their appropriate clinical indications as well as emerging technologies, strategies and products. Expert commentary : Recent years have been marked by dramatic and continuous progress towards the development of novel surgical sealant devices and their rigorous clinical testing. In addition, next-generation sealant formulations such as active hemostatic sealant patches and bio-inspired or nanoparticle-based sealant concepts have been developed and are constantly being evaluated and refined.